Response of Germination of Cocoa (Theobroma Cacao L.) Seeds to Types of Storage Media and Various Storage Times - Loso, Sugito; Ma'shum, Halim; Kriswantoro, Haris (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
Cocoa plants are plantation crops, one of the export commodities that can contribute to efforts to increase Indonesia’s foreign exchange. This research aims to determine the type of storage media, storage time and treatment interactions on the germination response of cocoa seeds. The research was carried out in Madang Village, Sumber Harta District, Musi Rawas Regency from February-March 2024. The research method used a Completely Randomized Factorial Design, the observation data was analyzed using R-Studio software. If the results of the variance test are significant at the 5% level, mean that the treatment shows a significant or very significant effect, then it will be continued with high significancy different test (HSD). The first factor consists of the type of storage media: without treatment (M0), sawdust storage media (M1), wood charcoal powder storage media (M2), and rice husk storage media (M3), the second factor is length of storage time: without treatment (W0), stored for 5 days (W1), stored for 10 days (W2), stored for 15 days (W3) and repeated 3 times. Based on the results of the research, sawdust storage media treatment had a significant effect on: germination at age 1-10 days and 11-20 days, root length, leaf length and leaf area; without storage treatment had a significant effect on: at age 1-10 days and 11-20 days, root length, leaf length, and leaf area.